2016
DOI: 10.7762/cnr.2016.5.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Lifestyle Factors and Iron Overload in Korean Adults

Abstract: It has been suggested that iron overload, which indicates the accumulation of iron, generates cellular reactive oxygens and causes peroxide damages to the body. Such oxidative stresses, in a broader context, are also caused by lifestyles such as alcohol consumption and smoking. However, there are limited data on the association between these lifestyle factors and internal iron overload. In present study, we evaluated associations between lifestyle factors, such as smoking status, alcohol consumption, and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
4
5
0
1
Order By: Relevance
“…Several studies have observed that some lifestyles, especially toxic habits, may alter iron status [23,59]. We noted that SF concentration was higher in participants who reported frequent alcohol consumption, which is consistent with previous results [61], although this association was not significant after adjusting for potential confounders.…”
Section: Diet and Lifestylesupporting
confidence: 92%
See 2 more Smart Citations
“…Several studies have observed that some lifestyles, especially toxic habits, may alter iron status [23,59]. We noted that SF concentration was higher in participants who reported frequent alcohol consumption, which is consistent with previous results [61], although this association was not significant after adjusting for potential confounders.…”
Section: Diet and Lifestylesupporting
confidence: 92%
“…We noted that SF concentration was higher in participants who reported frequent alcohol consumption, which is consistent with previous results [61], although this association was not significant after adjusting for potential confounders. In addition, we found a positive association between each daily 10-gram increase of alcohol and SF levels and the risk of excess iron, though only in males; this association has been reported before [62,63] and recently reinforced [23,24,64].…”
Section: Diet and Lifestylesupporting
confidence: 67%
See 1 more Smart Citation
“…Iron dysregulation is common in obesity [46], chronic liver disease [47], chronic kidney disease [48], and many cancers [49]. Heavy alcohol usage and smoking cigarettes can worsen iron excess in the body [50].…”
Section: Iron Dysregulation and Covid-19mentioning
confidence: 99%
“…Both heavy alcohol and smoking cigarettes can worsen iron accumulation in the body [112]. Heavy alcohol use is associated with increased cardiovascular risk, and excessive alcohol is the third leading cause of premature death (after smoking and obesity) in the U.S. [113].…”
Section: Iron and Risk Factors For Cardiovascular Diseasementioning
confidence: 99%